Determinan Tax Avoidance dengan CSR Disclosure sebagai Pemoderasi pada Perusahaan Manufaktur Terdaftar di Bursa Efek Indonesia - Darmansyah Simamora (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
The practices of tax avoidance that occur in Indonesia are very detrimental to the state. Based on data from Illegit Financial Flows from the Developing World: 2004 - 2013 released by Global Financial Integrity in 2014, Indonesia is ranked ninth from the most disadvantaged countries due to the exit money that should go into the state treasury during the period 2004-2013. The potential losses experienced by Indonesia during 2004-2013 are estimated at USD 180 billion. Of the above, 83.4% came from trade mis-invoicing including transactions aimed at avoiding taxes. The purpose of this study is to analyze transfer pricing, thin capitalization, tax haven utilization affecting tax avoidance, with moderated corporate social responsibility. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2016. Uses of Sampling is purposive sampling techniques, and the criteria have been determined. The subject of research is the manufacturing companies listed in the Indonesia Stock Exchange (IDX). The research result of transfer pricing has a significant effect on tax avoidance. Thin capitalization and tax heaven utilization have no significant effect on tax avoidance. Corporate social responsibility can moderate the effect of transfer pricing on tax avoidance. The other side, the Corporate social responsibility could not moderate the effect of thin capitalization and tax haven utilization on tax avoidance.